A sociological analysis of gender in Marxist theory - De Swardt, Cobus (Department of Sociology, 2016)
In this study I argue that Marxism has payed far too little attention to the influence of the gender division of labour on social structure. Consequently, Marxism has been unable to place women's exploitation within a general framework of exploitation, objectification and domination. In an attempt to overcome this shortcoming, I critically analyse the interaction of "labour" and "gender" within the structural framework of a contemporary capitalist patriarchal industrial society. My analysis is carried out within a materialist research tradition. I focus on the domestic mode of reproduction and production and analyse the gender division of labour in this mode. For this purpose I assess different theories of gender creation and the influence of mother-monopolized childrearing on gender creation and on the social structure in general. In working with the interaction of "labour" and "gender" I address the possibility of a gender-class analysis. For this purpose I reformulate the Marxist interpretation of the interaction between labour power, surplus value, exchange value and use value. I also assess the contribution of the wages-for-housework debate to a gender-class analysis. Finally I argue that "gender" makes a fundamental contribution to a possible understanding of the interrelation of exploitation, objectification and domination in a contemporary capitalist patriarchal industrial society.